Pemanfaatan Alat Pengupas Kulit Kopi untuk Membantu Kerja Manual Petani Kopi di Dusun Selelos, Kecamatan Gangga Lombok Utara - Ida Bagus Alit; I Gede Bawa Susana; Emmy Dyah S; Rudy Sutanto; Maharsa Pradityatama (Jurusan Teknik Mesin FT Universitas Mataram, 2024)
The use of smallholder plantation land in the North Lombok district is seen from the types of plants carried out by agricultural or plantation groups consisting of coconut plantations with an area of 10,574.62 tons and a production yield of 11,397.08 tons. Coffee plants with a planting area 1,315.57 with a production yield of 780.46 tons. Specifically for coffee plantations, farmers usually only process post-harvest through drying, after which they are immediately sold. To increase the selling value, it is necessary to utilise technological results such as using a coffee skin peeler. This tool helps increase the productivity of coffee farmers. The dedication will be carried out in Selelos Hamlet, Gangga sub-district, North Lombok district. The implementation of this service program includes making a coffee peeler, presentation, and counselling on using the tool, along with demonstrations. As a result, the coffee skin peeler has a production capacity of 100 kg per hour. The quality of the coffee beans produced is clean and free of impurities. The productivity of using a coffee skin peeler machine is greater and shorter when compared to the manual process.